High temperature fracture toughness and fatigue behavior of ti-zr-mo and w-re alloys for x-ray tube application - Harimon, Mohd Azhar (2017)
Commercial x-ray targets for computed tomography (CT) applications consist of two major components, a metal disc made of the titanium-zirconium-molybdenum (TZM) alloy, and a surface layer in the bombarding region made of the tungsten-rhenium (W-Re) alloy. The target must endure extremely high temperature, associated with high thermal stress, and mechanical stress due to the centrifugal force induced by high speed rotation of the target. Therefore, studies on high temperature fracture and fatigue behavior of these materials would be the most important for reliability assessment and safety design of the x-ray target. However, they have been rarely reported and high temperature fracture and fatigue behavior of these materials has been not always clarified. In the present study, high temperature fracture toughness was evaluated for two kind of TZM alloys, one with higher C content and the other with higher O content. Moreover, effect of forging rate on high temperature fracture toughness was discussed. Fatigue properties at room temperature and 1000 °C were evaluated for three kinds of materials, layered W-Re/TZM, bulk W-Re and bulk TZM, and a fatigue failure definition in the high temperature fatigue test was investigated to evaluate high temperature fatigue strength. The fatigue processes of these x-ray target materials at high temperature were also investigated. High temperature fracture toughness of two TZM alloys with different kinds of grain boundary particles was successfully evaluated using the convenient JIC test method. The result indicated that the JIC values at temperatures ranged from 800 °C to 1000 °C were almost constant regardless of temperature, while the JIC values of the TZM with higher C content were higher than those of the TZM with higher O content. The TZM with different forging rates showed similar JIC values, which suggested the effect of forging rate would be not significant at high temperatures.